37. Assistive Software for Disabled Learners - Clark, Sharon; Baggaley, Jon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Previous reports in this series (#32 and 36) have discussed online software features of value to disabled learners in distance education. The current report evaluates four specific assistive software products with useful features for visually and hearing impaired learners: ATutor, ACollab, Natural Voice, and Just Vanilla. The evaluative criteria discussed include the purpose, uses, costs, and features of each software product, all considered primarily from the accessibility perspective.